Sports medicine, performance enhancement and doping : a critical history - Waddington, Ivan; Brissonneau, Christophe (Routledge, Taylor & Francis Group, 2025)
Tracing the history of sports medicine from the ancient world through to the present day, this book shines new light on the embedded relationship between physicians, performance enhancement and doping in elite sport.Combining historical and sociological analysis, the book shows how sports medicine, as it developed in the late nineteenth and twentieth centuries, became increasingly disengaged from its origins in preventive medicine to become closely linked with elite level competitive sport. The book demonstrates how this link between sports medicine and elite competitive sport drew sports physicians into the search for enhanced performance so that by the second half of the twentieth century performance enhancement had become an essential raison d'tre of sports medicine practitioners. It examines how this search for enhanced performance has often led sports physicians to play a prominent role in the development and provision of performance-enhancing drugs, and looks in depth at the case study of France and professional cycling, scene of some of the most high-profile and consequential doping cases of all time.This book is fascinating reading for anybody with an interest in sport history, the history of medicine, medical ethics, the ethics of sport, sport and society, or science and society.